A case study on the management of UTM new hostel based on design and build arrangement - Mohamed, Nurul Hidayati (2005)
This study attempts to get the insight into the management design and build of UTM hostel. The objectives of the research are to identify the dominant procurement system in Malaysia, to study the management of design and build in UTM and to identify problems in UTM’s project related to design and build. This can be achieved by semi-structured interviews, unstructured discussion and questionnaires to garner a better understanding. This paper covers the traditional system is the most dominant procurement system in Malaysia followed by design and build and management contracting. While the management of the UTM hostel project was conducted fully by the project management consultant from the initial until the completion of the project and the main contractor was acted as the construction manager. The client just observed the activities and get involved when there is changes in cost and contract. The analysis of the problems encountered provides lessons to be learned for application to future projects.